STUDY ON THE COUPLING RELATIONSHIP OF POPULATION, RESOURCES, ENVIRONMENT AND ECONOMY IN HOHHOT-BAOTOU-ORDOS-ULANQAB URBAN AGGLOMERATION - Tojiyeva, Z.N.; Yongfeng, Zhao; Hui, Zheng (FAN va JAMIYAT, 2022)
This article states that the coupling and coordinated development among population, resources, environment and economic system is the important part of regional high quality development. The coupling degree of population-resources-environment-economy system in HBOUUA rised from running-in stage to high level coupling, and the coupling coordination degree changed from mild disorder to moderate coordination.